STUDENTS' LANGUAGE ATTITUDE IN MAINTAINING HERITAGE LANGUAGE - Alfian, Alfian (Eduscience : Jurnal Ilmu Pendidikan, 2021)
AbstractThe objectives of the research study were to determine the students 'attitude toward heritage language and to know students' habits in maintaining heritage language. A small-scale survey was carried out to probe students' language attitude in maintaining heritage language. 20 participants took part in this present study. The research data were collected through Two research instruments, they are: a questionnaire and a semi-structured interview. The finding showed that the students have positive language attitudes towards languages and maintain heritage language well, this is supported by the active role of students in preserving local languages in their respective environments. Keywords: students ‘language, attitude, heritage language AbstrakTujuan dari penelitian ini adalah untuk mengetahui sikap siswa terhadap bahasa daerah dan untuk mengetahui kebiasaan siswa dalam memelihara bahasa daerah. Survei skala kecil dilakukan untuk mengetahui sikap siswa dalam mempertahankan Bahasa daerah. 20 peserta mengambil bagian dalam penelitian ini. Data penelitian dikumpulkan melalui dua instrumen penelitian, yaitu: angket dan wawancara semi terstruktur. Hasil penelitian menunjukkan bahwa siswa memiliki sikap positif terhadap bahasa daerah dan memelihara bahasa daerah dengan baik, hal ini didukung oleh peran aktif siswa dalam melestarikan bahasa daerah di lingkungannya masing-masing. Kata kunci: bahasa siswa, sikap, bahasa daerah